A tractable model of precautionary reserves, net foreign assets, or sovereign wealth funds - Christopher D. Carroll; Olivier Jeanne (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We model the motives for residents of a country to hold foreign assets, including the precautionary motive that has been omitted from much previous literature as intractable. Our model captures many of the principal insights from the existing specialized literature on the precautionary motive, deriving a convenient formula for the economy's target value of assets. The target is the level of assets that balances impatience, prudence, risk, intertemporal substitution, and the rate of return. We use the model to shed light on two topical questions: The 'upstream' flows of capital from developing countries to advanced countries, and the long-run impact of resorbing global financial imbalances.
urn:nbn:de:hebis:30-68346
Keywords: C61; 330; Buffer Stock Saving; Net Foreign Assets; Sovereign Wealth Funds; Foreign Exchange Reserves; Small Open Economy Models; Sparen; Kassenhaltungsansatz; Auslandsvermögen; Währungsreserven; Staatsfonds; Kleines-offenes-Land; Theorie; Nord-Süd-Beziehungen; Kapitalmobilität; Welt